Literature Review: Pengaruh Konsumsi Fast Food terhadap Risiko Hipertensi pada Remaja - Sutanti Ira Cahyani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Hypertension in adolescents is a growing health problem that has the potential to persist into adulthood. One factor thought to play a role is the consumption of fast food, which is high in sodium, saturated fat and calories. This study aims to analyse the relationship between fast food consumption and the incidence of hypertension in adolescents using a literature review method. Data sources were obtained from Google Scholar and PubMed using the keywords “fast food”, “hypertension”, and “adolescents”. Inclusion criteria included full-text articles, original research, relevance to the topic, and publication between 2021 and 2026. Following the selection process, six journals were analysed. The review results showed that two journals (33.3%) found a significant association between fast food consumption and hypertension, whilst three journals (50%) found no significant association. Meanwhile, 1 journal (16.7%) indicated the presence of prehypertension in adolescents. These differing results suggest that hypertension in adolescents is multifactorial. It can be concluded that fast food consumption has the potential to increase the risk of hypertension, but this must be considered alongside other lifestyle factors.